Hospital-Based Community Health Education on Foot Care for Patients with Diabetes Mellitus - Yulia Indah Permata Sari; Luri Mekeama; Mutia Salsa Billa (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2024)
According to WHO, diabetes is a chronic metabolic disease characterized by elevated blood glucose (or blood sugar) levels, which over time causes serious damage to the heart, blood vessels, eyes, kidneys and nerves. Diabetic foot is one of the many complications of diabetes mellitus. We often see sufferers complaining that their feet feel sore, numb, cold, their feet look pale and wounds are difficult to heal. It is not uncommon for patients to have infected feet. This condition can be avoided with proper foot care. This service was held at RSUD H Abdul Manap on November 30 2023. The aim is for the target to be able to understand foot care for diabetes sufferers, and be able to apply it to everyday life. Foot care behavior is an action taken to maintain the cleanliness of the feet of diabetes mellitus patients and prevent early injury to the feet which can result in the risk of infection which, if not handled properly, could result in amputation. The total number of participants was 30 people. All service program activities run smoothly and are carried out well, and the location is suitable, and participants actively participate in these activities.